FACTORS ASSOCIATED WITH HEADACHES AMONG MEDICAL STUDENTS USING SMARTPHONES IN BURKINA FASO - Dabilgou, Alfred Anselme; Kyelem , Julie Marie Adeline Wendlamita; Dravé , Alassane; Karama, Kabako; Napon, Christian; Millogo , Athanase (Journal of Pain, Headache and Vertigo, 2024)
Smartphone misuse can cause neurological disorders, such as headaches. The objective was to study the prevalence and factors associated with headache among smartphone users in the medical students at the University Joseph Ki-Zerbo. This cross-sectional study was conducted between September 1 and December 31, 2023. A sample of 480 students was enrolled in the Medicine School of the University Joseph KI Zerbo. Of the 480 participants, 203 (42.3%) were high smartphone users (>4 h/24 h) and 277 (57.7%) The mean age was 23 ± 3.3 years. The majority of the students were male (64.79%). The duration of smartphone use was longer than 10 years in most studies (57.2%). Social networks were the most common reasons for smartphone use (48.75%). The prevalence of headache was 43.1%. The headache was unilateral (68.6%), pressure-type (64.3%) and moderate intensity (74.4%). Tension headache was the most common type of headache (81.6%). The headache had a moderate disability level (48.3%). Permanent mobile Internet (Odds ratio: 4,56 and IC95%: 2,83 to 7,32 ; p<0,001), high smartphone use (Odds ratio: 3,17 and IC95%: 1,92 to 5,22 ; p<0,001 ) and male sex (Odds ratio: 0,42 and IC95%: 0,25 to 0,70 ; p < 0,001) were associated with headaches. Headaches were common in medical students using smartphones. The factors associated with headaches were permanent mobile Internet, high smartphone use and male gender.